Genetic diversity analysis of soybean genotypes using SSR markers for salinity tolerance (Progressive Agriculture, 2019)
Soil salinity is a major constraint to soybean production. Five soybean genotypes were grown in pots with hydroponic culture under control and different salt stressed conditions to observe salt tolerance capacity on the basis of phenotypic screening and measure genetic diversity and relatedness among the genotypes. Minimum effects of salinity on root and shoot length was observed in Binasoyben-3, GC840 and Binasoyben-5at different salt stresses. Root dry weight and shoot dry weight of different soybean genotypes under different salt stresses were depicted. The highest reduction in root weight was noted in Binasoybean-1. The same genotypes were used to assess genetic diversity among them with simple sequence repeat (SSR) markers. A total of 33 alleles were detected among 5 soybean genotypes by using 10SSR markers. The number of alleles per locus ranged from 2 to 5, with an average of 3.33 alleles across the 10 loci. Rare alleles were observed at 10 SSR loci with an average of 2.8 alleles per locus. In this experiment, two SSR loci were found to be null alleles. The average values of null allele were 0.2. PIC values ranged from 0.27 in Satt184 to 0.77 in Satt339 with the average value of 0.56.The major allele frequency of the most common allele at each locus ranged from 0.80 in Satt184 to 0.20 in Satt339with a mean frequency of 0.48. The size of the different major alleles at different loci ranged from 173 bp for Satt509 to 407 bp for Satt339. The highest gene diversity (0.80) was observed in loci Satt339 and the lowest gene diversity (0.32) was observed in loci Satt184 with the mean diversity of 0.61. The lowest genetic distance (0.60) was observed in Asset vs Binasoybean-3 and Binasoybean-5 vs Binasoybean-3. The highest genetic distance (1.0) was observed between a numbers of genotype pairs with GC840 vs Asset. The UPGMA cluster analysis led to the grouping of the 5 genotypes into two major clusters. GC840, an advanced line identified to be salt tolerant, together with Binasoybean-5 and Binasoybean-3 clustered in the same sub group. The results from morphological and molecular study suggested that GC840 and Binasoybean-3 are moderately tolerant to salt stress.Progressive Agriculture 30 (1): 1-9, 2019